Optothermal microbubble assisted manufacturing of nanogap-rich structures for active chemical sensing. Issue 43 (22nd October 2019) - Karim, Farzia; Vasquez, Erick S.; Sun, Yvonne; Zhao, Chenglong
Abstract : Fabrication of nanogap-rich structures and active chemical sensing through an optothermally generated microbubble (OGMB). Abstract : Guiding analytes to the sensing area is an indispensable step in a sensing system. Most of the sensing systems apply a passive sensing method, which waits for the analytes to diffuse towards the sensor. However, passive sensing methods limit the detection of analytes to a picomolar range on micro/nanosensors for a practical time scale. Therefore, active sensing methods need to be used to improve the detection limit in which the analytes are forced to concentrate on the sensors. In this article, we have demonstrated the manufacturing of nanogap-rich structures for active chemical sensing. Nanogap-rich structures are manufactured from metallic nanoparticles through an optothermally generated microbubble (OGMB) which is a laser-induced micron-sized bubble. The OGMB induces a strong convective flow that helps to deposit metallic nanoparticles to form nanogap-rich structures on a solid surface. In addition, the OGMB is used to guide and concentrate analytes towards the nanogap-rich structures for the active sensing of analytes. An active sensing method can improve the detection limit of chemical substances by an order of magnitude compared to a passive sensing method. The microbubble assisted manufacturing of nanogap-rich structures together with an active analyte sensing method paves a new way for advanced chemical and bio-sensing applications.